Short-Chain Inulin Modulates the Cecal Microbiota Structure of Leptin Knockout Mice in High-Fat Diet - Feng, Yan; Feng, Jianghao; Wang, Lei; Meng, Ai; Wei, Siang; Cui, Jie; Hu, Xiongbing; Yan, Lihuan (Frontiers in Microbiology, 2021)
The aim of this study was to explore the effect of short-chain inulin on cecal microbiota of high-fat diet fed leptin knockout mice and the different influence of cecal microbiota in wild-type and leptin knockout mice. A total of 18 SPF male C57BL/6J wild-type mice and 18 C57BL/6J leptin knockout mice (OB/OB mice) were selected. Mice were divided into six groups according to their genotype, wild-type mice have three groups, including normal diet group (CT), 60% high-fat diet group (CH), 60% high-fat with10% short-chain inulin group (CHI); OB/OB mice were also divided into three groups, including normal diet group (OT), 60% high-fat diet group (OH), 60% high-fat with 10% short-inulin group (OHI). The mice were fed for 8 weeks to analyze the diversity of cecal microbiota. The results show that compared with CH and OH, the variety of cecal microbiota was significantly reduced in CH, OH and further reduced in CHI, OHI. Bifidobacterium and Lactobacillus are the biomarkers in genus level. Dietary short-chain inulin significantly enhanced Bifidobacterium in OHI compared with OH (P < 0.01), and significantly reduced in CHI and compared with CH (P < 0.01). Lactobacillus was significantly enhanced in CHI and OHI compared with CH and OH, respectively (P < 0.01). Blautia was significantly enhanced in CH and OH compared with other groups (P < 0.01). Both Escherichia-Shigella and Enterococcus were significantly reduced in CHI and OHI, compared with CH and OH respectively (P < 0.05). Escherichia-Shigella even lower than CT and OT in CHI and OHI. Functional prediction of microbial communities showed that the abundance of amino acid sugar and nucleotide sugar metabolism pathways were significantly enhanced (P < 0.05) in CH and OH, and OH was significantly higher than CH (P < 0.05). Among the leptin knockout groups, PICRUSt2 function prediction showed that fatty acid metabolism pathway significantly reduced (P < 0.05) in OHI and OT compared with OH. In conclusion, short-chain inulin modulated the dysbiosis induced by high-fat diet, improved probiotics growth and inhibited conditioned pathogenic bacteria, and the influences were significantly different in wild-type and leptin knockout mice.